PERANAN TANAMAN PENGHIJAUAN ANGSANA, BUNGUR, DAN DAUN KUPU-KUPU SEBAGAI PENYERAP EMISI PB DAN DEBU KENDARAAN BERMOTOR DI JALAN COKROAMINOTO, MELATI, DAN CUT NYAK DIEN DI KOTA DENPASAR - Sulasmini, Luh Komang; Mahendra, M.S.; Arthawa Lila, Komang (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 2 No 1)
The aim of this study was to observe the role of green trees to air quality in Denpasar City. The research locations were at Cokroaminoto, Melati, and Cut Nyak Dien streets, during February 2006 to July 2006. The sample plants were: angsanas, timber, and purple orchid leaf. Statistical analysis was conducted by applying double linier regression and anova test. The result showed that the highest total vehicle number (11.573 and 3.330), noise level (72,75 dB), air Pb concentration (0,313 ?g/m3), concentration of particulates (244 ?g/m3), temperature humidity index (27,45), wind speed (1,44 m/second), humidity (70,77 %), type and number of trees were observed at Cokroaminoto street (26 types and 866 trees), whilst the lowest values were at Cut Nyak Dien street (7 types and 121 trees). The highest temperature was observed at Melati street (29,25 oC) and the lowest was at Cut Nyak Dien street (28,51 oC). From the three places observed, the highest number of trees, height of tree, and width of crown were on angsanas tree (439 trees; 7,07 m; dan 8,7 m) and the lowest value was calculated on purple orchid leaf (14 trees; 4,60 m; dan 5,8 m). On the other hand the highest leaf wide was on timber (131,550 cm2) and the lowest on angsanas (42,745 cm2). Concentrations of Pb leaves were calculated as follows: angsanas 13,228 mg/kg; timber 13,208 mg/kg; purple orchid leaf 12,897 mg/kg, respectively. Statistical result showed that total plants, total motor cycle and total four wheels vehicles was not partially or simultaneously affected air Pb and air dirt concentrations. Height of tree, width of leaves and width of crown did not affect leaves Pb concentration both partially and totally to leaves Pb. Based on location, it can be concluded that there was no difference of air dirt and air Pb concentration, but there is difference in leaves Pb. Based on type of trees there was no significant difference on leaves Pb content among trees type, it means that every tree has similar ability in absorbing Pb.
Keywords: Green trees, Pb leaf, air Pb concentration, and dirt level.